The Influence of ESG, Green Finance, and Efficiency on Company Value Through Financial Performance at KBMI 3 and KBMI 4 Banks - Nainggolan, Putri Anandi; Siswanti, Indra (International Journal of Social and Management Studies, 2025)
This study aims to analyze the influence of three main factors—Environmental, Social, and Governance (ESG), green finance, and operational efficiency—on firm value, with financial performance as a mediating variable. The objects of this study were KBMI 3 and 4 banks listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research method used was a quantitative approach with secondary data, where the data were analyzed using path analysis and the Sobel test to test the mediation effect. The results of this study reveal several important findings. Directly, ESG has a negative and significant influence on firm value, but a positive influence on financial performance. Meanwhile, operational efficiency and green finance do not have a significant direct influence on firm value. However, both have a positive influence on financial performance. Specifically, this study found that financial performance is proven to positively mediate the influence of green finance and operational efficiency on firm value. However, financial performance is unable to mediate the influence of ESG on firm value. These findings contribute significantly to the literature by confirming that financial performance plays a crucial role in linking a company’s efficiency and sustainability strategies with increased firm value.